Ethical risks of using ChatGPT in higher education institutions in Malaysia - Mokhtar, Wan Khairul Aiman Wan; Ibrahim, Abdullah; Anas, Norazmi; Ahyar, Ahyar; Sayekti, Imam (Faculty of Social and Political Science, Universitas Airlangga, 2024)
Artificial Intelligence (AI) chatbot ‘ChatGPT’ in the education sector has changed the learning patterns among students, staff, and lecturers. The rise of AI-driven tools is bringing forth significant ethical concerns, which are considered essential to discuss. The present study was conducted in three public sector universities in Malaysia, where we opted for the quantitative research design and approached the research participants through personal invitation and snowball sampling procedures. A total of 406 respondents were involved in this study, and the data was gathered through a survey, using structured questionnaire. The purpose of this method is to collect diverse data from a variety of participants, including students, staff, and lecturers. The findings show that it is imperative to highlight the need for robust ethical guidelines and a higher education institution framework to ensure that implementation is indispensable. Furthermore, addressing these ethical challenges can harness the potential of chatbots in academia along with ensuring ethical concerns being addressed. The study concluded that academicians had clear understanding about the ethical issues of using ChatGPT or AIs. The study also suggests recommendations regarding the ethical usage by the government of Malaysia.